2016
DOI: 10.4191/kcers.2016.53.2.222
|View full text |Cite
|
Sign up to set email alerts
|

Precipitated Calcium Carbonate Synthesis by Simultaneous Injection to Produce Nano Whisker Aragonite

Abstract: The synthesis of pure calcium carbonate nanocrystals was achieved using a simultaneous injection method to produce nano particles of uniform size. These were characterized using scanning electron microscopy and powder X-ray diffraction. The nano particles were needle-shaped aragonite polymorphs, approximately 100-200 nm in length. The aragonite polymorph of calcium carbonate was prepared using aqueous solutions of CaCl 2 and Na 2 CO 3 , which were injected simultaneously into double distilled water at 50°C and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
1
16
0
2
Order By: Relevance
“…Recently, Ramakrishna et al (2016) observed the formation of polymorphs according to the temperature, reaction time, and pH using 0.1 M CaCl2 and 0.1 M Na2CO3 solutions at 25 to 50°C and at pH 10-12. They reported that pH 10 is the most suitable condition for obtaining pure aragonite, whereas calcite became the dominant polymorph when pH exceeded 10.…”
Section: Effect Of Ph On the Formation Of Caco3 Polymorphsmentioning
confidence: 99%
“…Recently, Ramakrishna et al (2016) observed the formation of polymorphs according to the temperature, reaction time, and pH using 0.1 M CaCl2 and 0.1 M Na2CO3 solutions at 25 to 50°C and at pH 10-12. They reported that pH 10 is the most suitable condition for obtaining pure aragonite, whereas calcite became the dominant polymorph when pH exceeded 10.…”
Section: Effect Of Ph On the Formation Of Caco3 Polymorphsmentioning
confidence: 99%
“…40-42 2. High pH conditions, greater than pH 11, are favorable for calcite formation, [40][41][42][43] hence carbonate solution produced through DAC with a pH of 13.9 is favorable. 3.…”
Section: Carbonate Crystallization and Polymorphismmentioning
confidence: 99%
“…In view of the intended use of carbonate ion capture through DAC for CaCO 3 precipitation for ground improvement, the precipitation condition would be at an ambient condition of 1 atm and 20°C (300 K). Literature assessing calcite precipitation potential under these synthesis conditions has concluded the following: Synthesis temperature around 20–25°C is favorable for calcite formation High pH conditions, greater than pH 11, are favorable for calcite formation, hence carbonate solution produced through DAC with a pH of 13.9 is favorable. Potassium hydroxide ionic strength is lower than that of sodium or other metals, hence promoting calcite yield …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, calcium carbonate of the required quality is more frequently obtained by chemical methods. Two of the most widespread methods to obtain CaCO 3 are the carbonization of natural dolomite or other calcium-containing raw materials (Chilakala et al 2016;Teir et al 2016) and the chemical precipitation by mixing soluble calcium salts (calcium chloride or nitrate) with sodium carbonate in an aqueous medium (heterogeneous precipitation) (Kawano et al 2009;Ramakrishna et al 2016;Prasetia et al 2017). The sources of calcium can be industrial wastes such as: concrete waste (Van der Zee and Zeman 2016), steel production wastes (Teir et al 2016;Said et al 2013;Mattila and Zevenhoven 2014), spent marble crumb (Erdogan and Eken 2017), soda production wastes (Mikhaylova et al 2004;Molchanov et al 2006), etc.…”
Section: Introductionmentioning
confidence: 99%